Improving overall equipment effectiveness of tesec test handler on unloader jamming reduction at LPL testing area using DMAIC approach - Maria Amirtha Raj, Michel Raj (2017)
Infineon Technologies Melaka today makes great financial investments in testing their processes and systems to ensure that they will meet customer expectations. The corporations go through all the precise steps to test as thoroughly as possible at a time in many cases at the end consequences are less than anticipated for the effort, time and dollars expended where the cost of manufacturing semiconductors continues to increase and has become a main concern in the industry is to do amount of cost saving. The company have been industrialized to reduce cost of test and to keep forward of the competitors. The most common metric used by managements to measure the main effectiveness and success of the TPM is the Overall Equipment Effectiveness (OEE) in Semiconductor Company throughout the world. In spite of having expertise of skilled manpower and high performance fool proof machines yet the production equipment’s still have problematic issues that causes the low performance on the OEE. The objective of the study is to narrow down by defining the major breakdown which causes the handler jamming and find the root cause of the defect, by proper trouble shooting on the test handler which could eliminate jamming and eventually improve the OEE. The DMAIC approaches will systematically applying Define, Measure, Analyse, Improve and Control as it adapts to recognized source of the problem at the defined stage where it provides a systematic methodology. To achieve permanent solution, step by step analysis performed to detect the real root cause eventually could improve OEE and eliminate the jamming of the test handler.